Implementasi Gerakan Literasi Madrasah pada Literasi Baca Siswa Kelas III MI Nurul Huda Balai Gajah - Aulia, Miranti; Aslamiah, Rabi’atul; Dzuhry, Robi’ul (Jurnal al Muta'aliyah: Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This study aims to describe the implementation of the School Literacy Movement (GLS) in strengthening reading literacy among third-grade students at MI Nurul Huda Balai Gajah. The study is grounded in the urgency of reading literacy as a foundation of students’ academic abilities, as well as various findings indicating the low level of literacy achievement in elementary schools. The research adopts a descriptive qualitative approach, with data collected through non-participatory observations, semi-structured interviews, and documentation. Data were analyzed using the Miles, Huberman, and Saldana model, which includes data reduction, data display, and conclusion drawing. The findings show that the implementation of GLS is carried out through 15-minute reading activities, the provision of reading corners, and the integration of literacy into learning activities. However, the implementation has not been fully optimal due to limited literacy facilities, variations in student motivation, and teachers’ time management challenges. Supporting factors include teacher commitment and a conducive school environment, while the main obstacles involve the limited collection of reading materials and inconsistent program execution. This study concludes that GLS has strong potential to enhance students’ reading literacy, yet it requires improved facilities, more targeted pedagogical strategies, and broader involvement of the entire school community